Implementasi Teori Behaviorisme pada Pembelajaran Matematika dalam Mengembangkan Kecakapan Abad 21 Pada Siswa Sekolah Dasar - Noor, Naili Luma'ati (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
Current learning, including mathematics, is required to encourage students to have 21st century skills in the form of communications, creative thinking, critical thingking, and collaborations. Because it needs a good learning process that is able to develop these skills. This study aims to examine how to develop 21st century skills in MI Hikmatun Najah students through the theory of behaviorism in learning mathematics. This research is a qualitative method using a case study design. The techniques used in data collection are tests, observation, and documentation. Data analysis was performed using data reduction, data presentation and conclusion. The results of this study indicate that developing students' 21st century skills cannot be separated from various factors in the school environment, both the role of the school, teachers, students, and society. Implementation of behaviorism learning theory in learning mathematics is an alternative in developing 21st century skills that are tailored to the goals and needs of learning. By providing a stimulus in the form of learning activities that refer to 21st century skills, it results in changes in behavior that are in line with 21st century skills